The Effect of Organizational, Individual, and Job Characteristics on Organizational Commitment with Job Satisfaction as an Intervening Variable (Study on Employees of PT. Sukses Mantap Sejahtera (SMS) Dompu Regency) - Haryono (CV. AFDIFAL MAJU BERKAH, 2022)
This study aims to explain the effect of organizational characteristics, individual characteristics, and job characteristics on organizational commitment with job satisfaction as an intervening variable at PT. Success Steady Prosperous Dompu Regency. The method used in this study is a quantitative method with a population of 300 people. The sample used in this study used a census technique which took the total number of samples as respondents, which was 300 people. Data analysis techniques were used in this study, namely descriptive statistical analysis, classical assumption test, and path analysis (Path Analysis) using the SPSS version 26 program. From the test results obtained results 1) Organizational Characteristics have a direct and significant effect on Job Satisfaction with a significance value of 0.000. 2) Individual Characteristics have a direct and significant effect on Job Satisfaction with a significance value of 0.032. 3) Job characteristics have a direct and significant effect on job satisfaction with a significance value of 0.009. 4) Job Satisfaction has a direct and significant effect on Organizational Commitment with a significance value of 0.022. 5) Organizational Characteristics have a direct and significant effect on Organizational Commitment with a significance value of 0.000. 6) Individual Characteristics have a direct and significant effect on Organizational Commitment with a significance value of 0.045. 7) Job characteristics have a direct and significant effect on Organizational Commitment with a significance value of 0.012. 8) Organizational characteristics have an indirect and significant effect on Organizational Commitment through Job Satisfaction with a significance value of 0.004. 9) Individual characteristics have an indirect and significant effect on Organizational Commitment through Job Satisfaction with a significance value of 0.008. 10) Job Characteristics have an indirect and significant effect on Organizational Commitment through Job Satisfaction with a significance value of 0.006.